Elevating Employee Performance: The Role of Soft Skills in Optimizing Performance at Tikur Anbesa Specialized Hospital in the Ethiopian Health Sector: Mediating Role of Compassion Satisfaction and Patient Health Literacy - Seid, Rahma Ahmed; Kero, Chalchisa Amentie; Nemera, Gemechu; Mohammed, Endres Ahmed (International Review of Management and Marketing, 2026)
Soft skills such as communication, empathy, and teamwork are essential in the healthcare setting, influencing employee performance and patient outcomes. Previous studies have investigated the role of soft skills in employees’ performance across various organizational contexts. However, translating soft skills into higher employee performance, particularly through parallel mediating mechanisms in the hospital setting, has received limited attention. This study aimed to investigate the effect of soft skills on employee performance and to explore the mediating role of compassion satisfaction and patient health literacy. The study used a cross-sectional quantitative design with 313 health professionals, selected through stratified random sampling at Tikur Anbesa Specialized Hospital, Ethiopia. A survey questionnaire was used to collect data, and structural equation modeling (SEM) was employed to evaluate the direct and indirect relationships among variables. The findings indicate that all soft skills, communication, empathy, and teamwork, are positively related to health workers’ performance. Moreover, these soft skills foster compassion satisfaction and patients’ health literacy, thereby enhancing the task and contextual performance of health employees. As such, compassionate satisfaction and patient health literacy serve as a conduit through which soft skills are translated into higher performance in a hospital setting. These results suggest that enhancing healthcare workers’ soft skills is crucial for enhancing their task and contextual performance, both directly and indirectly through improved patient health literacy and compassionate satisfaction. As such, the study contributes to existing literature and expands our understanding of the positive role of soft skills as drivers of health professional excellence in hospitals where resources are limited and the working environment is challenging. Establishing healthcare policies and training programs to maximize soft skills will have practical implications for healthcare employees, patients, and human resource development programs in public hospitals.